Assessment of risk factors among female patients with various Acute Coronary Syndrome types presenting to Cardiology unit DHQ Kohat, Pakistan. - Qaisar Ali Khan; Noman Khan; Arif Mumtaz; Naseer Ahmad; Nowshad Asim; Asmat Shaheen; Ameena Arif (International Journal of Endorsing Health Science Research, 2022)
Background: There is limited literature regarding the risk factors associated with acute coronary syndrome among female patients of the region, while none was previously reported from Kohat, Pakistan. Therefore, the present study aims to assess the risk factors among female patients with various types of Acute Coronary Syndrome (ACS).